Differential influences of prism adaptation on reflexive and voluntary covert attention - Striemer, Christopher; Sablatnig, Jeffery; Danckert, James (My University, 2006)
Recent research has demonstrated some beneficial effects in patients with neglect using rightward shifting prismatic lenses. Despite a great deal of research exploring this effect, we know very little about the cognitive mechanisms underlying prism adaptation in neglect. We examined the possibility that prism adaptation influences visual attention by having healthy participants complete either a reflexive or a voluntary covert visual attention cuing paradigm before and after adaptation to leftward, rightward, or sham (no shift) prisms. The results for reflexive orienting demonstrated that a subset of participants with large cuing effects prior to prism adaptation were faster to reorient attention away from an invalid cue on the side of space opposite the prismatic shift post adaptation. For voluntary orienting, left prisms increased the efficiency of voluntary attention in both left and right visual space in participants with a small cuing effect prior to prism adaptation. In contrast, right prisms decreased the efficiency of voluntary attention in both left and right space for participants with a large cuing effect prior to prism adaptation. No significant effects were observed in the sham prisms groups. These results suggest that prism adaptation may exert a variety of influences attentional orienting mechanisms.
Keywords: neglect; parietal lobes; visuomotor adaptation; spatial representation; perceptual disorders; sensory motor performance